Bioeroding sponge assemblages: the importance of substrate availability and sediment. (22nd March 2018) - Marlow, Joseph; Schönberg, Christine H.L.; Davy, Simon K.; Haris, Abdul; Jompa, Jamaluddin; Bell, James J.
Abstract : Despite global deterioration of coral reef health, not all reef-associated organisms are in decline. Bioeroding sponges are thought to be largely resistant to the factors that stress and kill corals, and are increasing in abundance on many reefs. However, there is a paucity of information on how environmental factors influence spatial variation in the distribution of these sponges, and how they might be affected by different stressors. We aimed to identify the factors that explained differences in bioeroding sponge abundance and assemblage composition, and to determine whether bioeroding sponges benefit from the same environmental conditions that can contribute towards coral mortality. Abundance surveys were conducted in the Wakatobi region of Indonesia on reefs characterized by different biotic and abiotic conditions. Bioeroding sponges occupied an average of 8.9% of available dead substrate and variation in abundance and assemblage composition was primarily attributed to differences in the availability of dead substrate. Our results imply that if dead substrate availability increases as a consequence of coral mortality, bioeroding sponge abundance is also likely to increase. However, bioeroding sponge abundance was lowest on a sedimented reef, despite abundant dead substrate. This suggests that not all forms of coral mortality will benefit all bioeroding sponge species, and sediment-degraded reefs are likely to be dominated by a few resilient bioeroding sponge species. Overall, we demonstrate the importance of understanding the drivers of bioeroding sponge abundance and assemblage composition in order to predict possible impacts of different stressors on reefs communities.